Pengaruh Live Streaming Tiktok Sebagai Aplikasi Komunikasi Digital Dan Dampaknya Pada Purchase Intention (Studi Kasus Brand Senikersku) - Paulus, Aprianer (Institut Agama Kristen Negeri Kupang, 2024)
The digital age brings significant changes with the advent of computer information technology and the internet. Digital media provides easier and faster access to information, allowing direct interaction between individuals and organizations through various platforms, including TikTok live streaming. TikTok has become popular as a digital communication platform that allows brands to interact directly with consumers, including in the context of the Snikersku brand. This study aims to analyze the effect of TikTok live streaming as a digital communication application on consumer purchase intention for skincare products for Brand Senikersku. This research uses a descriptive analysis method with a qualitative approach, mainly through literature study. Data was collected from various sources such as books, journals, the internet, and previous research to gain a deeper understanding of the influence of TikTok live streaming on consumer purchase intention. The results showed that TikTok live streaming has a significant influence on consumer purchase intention towards Brand Senikersku. Direct interaction between brands and consumers, as well as entertainment and product visualization presented in live streaming, play an important role in increasing consumer purchase intention. In TikTok live streaming, entertainment and product visualization are key to influencing consumer purchase intentions. The combination of live interaction, entertainment, and product information increases brand awareness, builds trust, and increases sales for the Snikersku brand.